Kemandirian Guru dalam Mengembangkan Materi PAI Berbasis Teknologi di MTs Negeri 1 Kabupaten Gorontalo - Listi Astuti Talibo; Sri Wahdini; Supriadi A. Tambanusu; Najamudin Petta Solong (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2024)
Islamic Religious Education (PAI) as an integral part of the educational curriculum requires teacher independence in developing learning materials that are relevant to current developments. This article investigates the role of teacher independence in developing technology-based PAI materials in MTs. Negeri 1 Gorontalo Regency. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews and document analysis. The research results show that teacher independence in adopting technology as a PAI learning aid plays an important role in improving the quality of teaching. Factors such as technological skills, motivation, and institutional support influence the level of teacher independence. This article concludes that teacher empowerment in terms of technological skills and institutional support are the main keys in developing PAI materials that are innovative and relevant to students' needs in the digital era.